2023
DOI: 10.3389/fpubh.2022.1067038
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative experiences with the COVID-19 pandemic among lonely and non-lonely populations in Germany

Abstract: The COVID-19 pandemic is causing an epidemic of loneliness. Previous studies have shown the differences in positive and negative experiences of lonely and non-lonely people in a non-pandemic setting. However, it is unclear how the drastic alteration of the COVID-19 pandemic may influence peoples' reactions and beliefs, especially among those who feel lonely. Our study aims to examine the positive and negative experiences among lonely and non-lonely people. We undertook a cross-sectional online survey of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…A total of 14 studies investigated the association between loneliness and negative emotions. Among these, one study was conducted in adolescents (Baytemir and Yildiz, 2017 ), four studies were conducted in young adults (Durak and Senol-Durak, 2010 ; Satici 2019 ; Tan et al ., 2020 ; Shi et al ., 2023 ), four were conducted in middle-aged adults (Ben-Zur 2012 ; Velotti et al ., 2021 ; Mikocka-Walus et al ., 2021 ; Wegner and Liu, 2023 ), and five were conducted in older adults (Steptoe et al ., 2011 ; Neto 2014 ; Serra et al ., 2021 ; Hoffman et al ., 2021 ; Badal et al ., 2022 ). All 14 studies reported a positive relationship between loneliness and negative emotions among healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 14 studies investigated the association between loneliness and negative emotions. Among these, one study was conducted in adolescents (Baytemir and Yildiz, 2017 ), four studies were conducted in young adults (Durak and Senol-Durak, 2010 ; Satici 2019 ; Tan et al ., 2020 ; Shi et al ., 2023 ), four were conducted in middle-aged adults (Ben-Zur 2012 ; Velotti et al ., 2021 ; Mikocka-Walus et al ., 2021 ; Wegner and Liu, 2023 ), and five were conducted in older adults (Steptoe et al ., 2011 ; Neto 2014 ; Serra et al ., 2021 ; Hoffman et al ., 2021 ; Badal et al ., 2022 ). All 14 studies reported a positive relationship between loneliness and negative emotions among healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in findings might be caused by the latter study specifically testing the relationship between loneliness and negative symptoms under the COVID-19 pandemic. Furthermore, one study showed that loneliness as measured using ULS-20 was positively correlated with general negative emotions (Ben-Zur 2012 ; n = 196, mixed-sex), and another study showed that loneliness as measured using ULS-8 was positively associated with distress emotions to the COVID-19 pandemic (Wegner and Liu, 2023 , n = 1354, mostly females).…”
Section: Resultsmentioning
confidence: 99%